2014
DOI: 10.1590/s0100-39842014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Complete internal audit of a mammography service in a reference institution for breast imaging

Abstract: ObjectiveUndertaking of a complete audit of the service of mammography, as recommended by BI-RADS®, in a private reference institution for breast cancer diagnosis in the city of São Paulo, SP, Brazil, and comparison of results with those recommended by the literature.Materials and MethodsRetrospective, analytical and cross-sectional study including 8,000 patients submitted to mammography in the period between April 2010 and March 2011, whose results were subjected to an internal audit. The patients were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
1
23
2
Order By: Relevance
“…When compared to other studies [14][15][16] , the present study observed a greater proportion of mammograms classified as BI-RADS 3 and 4 and a similar number of BI-RADS 5 mammograms. Some factors may be considered to explain this result.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…When compared to other studies [14][15][16] , the present study observed a greater proportion of mammograms classified as BI-RADS 3 and 4 and a similar number of BI-RADS 5 mammograms. Some factors may be considered to explain this result.…”
Section: Discussioncontrasting
confidence: 52%
“…However, it is observed that results of different centers are not the same 16 . Thus, studies that use data from several services 14,16 may be subject to greater heterogeneity than those evaluating a single center 15 . Moreover, the different socioeconomic realities found in our country may contribute so that the screening is offered in an unequal way in different locations, influencing the rate of tumor detection 10,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, as previously mentioned, the incidence of breast cancer among women aged 40-50 years in Brazil and other developing countries is proportionally higher than that reported in developed countries. 3,5 Therefore, the CBR, SBM and FEBRASGO recommend that this group of women be included in breast cancer screening protocols in Brazil.…”
Section: Justificationmentioning
confidence: 99%
“…1,2 In Brazil, despite all efforts, an increase in both breast cancer incidence and mortality rates has been noticed. [3][4][5] One peculiarity of breast cancer in Brazil and in other developing countries is that its incidence among women aged 40-50 years is proportionally higher than that reported in developed countries. [6][7][8] Programs that aim at standardizing breast cancer screening guidelines -as well as educating the population regarding the importance of such tests -should be promoted.…”
Section: Introductionmentioning
confidence: 99%